Corporate social responsibility actions in times of pandemic - Martins, Andréia Ferreira (2021)
The Covid-19 pandemic has been causing relevant impacts around the world since 2020, not only in people's habits, but mainly in companies; which has been taking measures to prevent contamination of its employees, customers and suppliers. In this context, this article aims to understand and investigate how companies mobilized in the face of an adverse crisis scenario and to analyze the actions and measures taken to cope with the guidelines of the WHO and the main guidelines for corporate social responsibility guidelines -CSR. The investigation performs a contextualization and theoretical review of Corporate Social Responsibility in the context of the pandemic and the corporate actions that were implemented by the surveyed companies. It is a qualitative exploratory research, carried out in three companies from different business sectors, chosen for convenience; being the data collected through semi-structured questionnaires, with the elaboration of a content analysis; later presented summarized in individual tables. The results are basically presented in the confirmation that the companies surveyed only adopted the basic measures of the WHO recommendations: mandatory use of masks, social distancing when possible and availability of alcohol gel. Effective communication and corporate social responsibility actions are not identified by companies, seeking to mitigate the risks of invite-19, with its employees, customers and suppliers. The study's restrictions are related to the choice for convenience of the companies, and the choice of the respondent in the companies, which can distort the data collected; even though new lines of research are emerging, as companies continue to be immersed in the pandemic, in the quest to better understand the communication mechanisms adopted by companies and the failures of communication incurred by companies. Finally that the objective proposed in the investigation was fully achieved.